A nip of murder : a moonshine mystery - Miller, Carol, 1972- (Moonshine mystery series, 2014)
"As Daisy McGovern knows all too well, it isn't easy being a young, small town waitress at the local diner. And it becomes even harder just as she's trying to stitch her life back together and salvage her job by converting the diner into a bakery when a mysterious robbery occurs and one of the thieves ends up dead on the bakery floor with a chef's knife in his chest. Forced into a twisted game of cat-and-mouse that takes her from secretive nip joints overflowing with moonshine to weathered Appalachian mountaintops overflowing with history and guns, Daisy must figure out who the dead man is--and why he was in her bakery--before she becomes the next victim. This is the second entry in a charming series filled with eccentric characters, red herrings, and, of course, moonshine!"--